BUILDING A WEB-BASED ALUMNI INFORMATION SYSTEM IN INDONESIA: STUDY AT SMK NW TEMBENG PUTIK - Muhammad Anshori (Scientium Educational Review, 2022)
Considering that the relationship between alums and schools has not been appropriately managed, it is necessary to answer problems related to the feasibility of the alumni information system from the user aspect and how the alumni information system from the literature study. Based on a literature study examining alumni information systems development using analysis, design, implementation, and testing, 2 (two) conclusions are generated. First, the feasibility of the alum information system from the user aspect is sufficient to use the web because the web-based alumni information system can track the whereabouts and register alums. Second, the feasibility of the alumni information system from the literature study shows that prioritizing functional suitability is more adequate than other aspects. It is based on these aspects, which have the characteristics of the extent to which a set of functions covers all the tasks and user-defined objectives and the extent to which a product or system delivers the correct results with the required precision.